Features of the use of probiotics for antibiotic-associated diarrhea in children - S.L. Nyankovskyy; О.S. Nyankovska; M.S. Yatsula; M.I. Horodylovska; Ya.V. Tomkiv; H.Z. Vivcharivska; V.D. Shaidych; O.M. Horayska; L.V. Zastavna; Z.V. Tomkiv (Zaslavsky O.Yu., 2020)
Antibiotic-associated diarrhea arises when the antibiotic disrupts the ecology of the intestinal microbiota, by altering the diversity and number of bacteria in the gut. These changes can affect the capacity of the resident microbiota to resist the invasion of pathogenic microorganisms or the overgrowth of opportunistic pathogens species that are endogenously present in the microbiome. Therefore, antibiotic-associated diarrhea may result in prolonged hospitalization, increased health care costs and other complications. Diarrhea is most frequently associated with the use of broad-spectrum antibiotics. Probiotics are "live microorganisms that, when administered in adequate amounts, confer a health benefit on the host". Numerous clinical researches evaluate the efficacy of Lactobacillus rhamnosus GG in the prevention of antibiotic-associated diarrhea. The aim of our research was to study the efficacy of the probiotic Probiolog Baby in children aged from 4 months to 9 years with antibiotic-associated diarrhea, and to investigate its effect on dysbiotic bowel changes. We observed 28 children aged from 4 months to 9 years (average age 4.6 ± 1.9 years) with antibiotic-associated diarrhea, including 57 % of boys and 43 % of girls. The children received the probiotic Probiolog Baby - 1 stick daily for 10 days. In 10 days, only 2 children (7.2 %) had complaints about diarrhea against 100 % at the beginning of our research. The use of Lactobacillus rhamnosus GG (ATCC 53103) in children with antibiotic-associated diarrhea helps reduce diarrhea, colic, bloating, nausea, vomiting, anxiety and poor sleep in children. Considering the combined effect of Lactobacillus rhamnosus GG strain, it can be argued that Probiolog Baby increases the levels of bifidobacteria and lactobacilli in the stool and also reduces the growth of Candida and pathogenic intestinal flora.